\(y^2+2xy-3x-2=0\)
\(\Leftrightarrow\left(y^2+2xy+x^2\right)-\left(x^2+3x+2\right)=0\)
\(\Leftrightarrow\left(x+y\right)^2=\left(x+1\right)\left(x+2\right)\)
\(\Leftrightarrow\left[{}\begin{matrix}x+1=0\\x+2=0\end{matrix}\right.\)
Nếu \(x+1=0\) thì \(\left\{{}\begin{matrix}x=-1\\y=1\end{matrix}\right.\).
Nếu \(x+2=0\) thì \(\left\{{}\begin{matrix}x=-2\\y=2\end{matrix}\right.\)
Thử lại, ta thấy thỏa mãn. Vậy ta tìm được các cặp số \(\left(x;y\right)\) thỏa mãn đề bài là \(\left(-1;1\right),\left(-2;2\right)\)